EU labour migration in troubled times skills mismatch, return, and policy responses - Galgoczi, Bela; Leschke, Janine; Watt, Andrew (Ashgate Pub., 2012)
This title studies the skills and qualifications of migrant workers within the European Union (EU) and how they interact with the duration of migration. The book contains quantitative-empirical chapters - which look at transversal rather than national issues - as well as comparative policy chapters.